Effects of electronic resources on the reading interests of the 4th year high school students of La Immaculada Concepcion School in Pasig City - Belo, Blesilda D.; Gonzales, Grace Marie B. (Quezon City : Institute of Library Science, University of the Philippines Diliman, 2001)
This is a study on the effects of electronic resources on the reading interests of the 4th year high school students of the La Immaculada Concepcion School. Sample of the study consists of 95 students, 30 of whom are male and 65 female. Almost all these students belong to the same age bracket and come from middle to upperclass families.
The objectives of this study are to know the kinds of reading materials that 4th year high school students of the LICS read, the types of electronic resources used by these students, the effects of the electronic resources on the reading interests of these students, and what recommendations can be given to promote the reading activities and the use of electronic resources. This study follows a descriptive method, wherein questionnaires were given to a random sample of ninety-five students to find out about their reading interests and their use of electronic resources. Statistical analysis used is the Goodness-of-Fit Test or the Chi-Square Test (for contingency tables).
Results of the study show that the students read frequently to seldom almost all types of print materials such as the newspapers, magazines, textbooks, encyclopedias, pocketbooks or paperbacks and other reading materials. Many of them read broadsheet newspapers; magazines that are about fashion and general information; the English and El Filibusterismo textbooks; the Brittanica encyclopedia; pocketbooks that are about lovestories or romance, humor and adventure; and other reading materials such as the dictionary. They have used electronic resources such as on-line journals and the CD-ROMs and many of them have used the Encarta Multimedia CD-ROM. The students used both these materials, for (in order of importance) information, learning, recreation and other purposes. The respondents' subject preferences in general are: fashion, romance, adventure, music and history. The students who used the electronic resources have lesser subject preferences than those who did not, but when it comes to the types of materials they read, there is no significant difference.
Lastly, the recommendation of this study for the reading interests of the students is to treat some reading materials like textbook and encyclopedias as fun to read or something recreational so that it would not be boring to read. Since electronic resources according to the students are also used for information and learning, they should be used by the students to complement their study.
Vita.
Thesis (Bachelor of Library and Information Science)--University of the Philippines Diliman
Keywords: Electronic information resources; La Immaculada Concepcion School; Reading interests -- Philippines -- Pasig City